2018
DOI: 10.1002/pc.24749
|View full text |Cite
|
Sign up to set email alerts
|

Eco‐friendly composites derived from naturally occurring molecules in promoting dispersion of nanosized silica particulates

Abstract: The reinforcement of highly dispersible silica (HDS) in Natural rubber was hindered by their high polarity and hydrophilic surface of the filler. We addressed this challenge by developing a Terpene phenolic resin functionalized Natural rubber (TNR) coupled with epoxidized natural rubber (ENR) composites. The loading of the HDS were considered from 40 to 60 phr (parts per hundred rubber). The uniform distribution of the HDS within the rubber blends in the absence of silane coupling agent and process oil was pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…2(f) revealed a reasonable epoxidation degree (about 13.8%). Except for chemical interactions, the physical interactions between the introduced functional groups and silanol groups in silica, such as hydrogen‐bond interactions and acid–base interactions, also led to enhanced interfacial interaction and improved dispersion of silica 50–52 …”
Section: Recent Progress Of Elastomer–silica Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…2(f) revealed a reasonable epoxidation degree (about 13.8%). Except for chemical interactions, the physical interactions between the introduced functional groups and silanol groups in silica, such as hydrogen‐bond interactions and acid–base interactions, also led to enhanced interfacial interaction and improved dispersion of silica 50–52 …”
Section: Recent Progress Of Elastomer–silica Nanocompositesmentioning
confidence: 99%
“…Except for chemical interactions, the physical interactions between the introduced functional groups and silanol groups in silica, such as hydrogen-bond interactions and acid-base interactions, also led to enhanced interfacial interaction and improved dispersion of silica. [50][51][52] Compared with in-chain functionalization, end-chain functionalization has the following advantages. First, end-chain functionalization occurs at the end of polymer chains, avoiding the destruction of the main polymer chains.…”
Section: Silica Dispersionmentioning
confidence: 99%
“…Consequently, a number of techniques have been developed to increase the dispersion of silica in the rubber matrix. These methods include the use of coupling agents, [15][16][17] the addition of a second ller, 11,18,19 and the improved interface structure. 20,21 The stirred tank is a key equipment for the wet process, with ow behavior and mixing in the system directly inuencing product quality.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a number of techniques have been developed to increase the dispersion of silica in the rubber matrix. These methods include the use of coupling agents, 15–17 the addition of a second filler, 11,18,19 and the improved interface structure. 20,21…”
Section: Introductionmentioning
confidence: 99%
“…Terpenoids are biologically-sourced olefins that hold great promise for supplanting fossil fuel-derived olefins in tars and bitumen used in asphalt, in polymers, and in related composite materials [1][2][3][4][5][6][7][8][9]. In previous work we demonstrated that monoalkene, diene and triene terpenoids react with sulfur to yield durable composites having compressive strengths that can exceed that of ordinary Portland cement (OPC) [10,11].…”
Section: Introductionmentioning
confidence: 99%